Pengaruh pH Air Perendam Pada Proses Perkecambahan Terhadap Karakteristik Kimia dan Fungsional Tepung Kecambah Kacang Tunggak (Vigna unguiculata) - Rahma Putra, Febrian; Wisaniyasa, Ni Wayan; Mayun Permana, I Dewa Gde (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPA, 2022)
This study aims to know the effect of pH water immersion on the germinated cowpea flour characteristics and to know which pH water that can produce a germinated cowpea flour with the best characteristics. This research used a Complete Randomized Design with a different pH water for immersion as the treatment, which is pH 3, pH 5, pH 7,pH 9 and pH 11. The experimentation was repeated 3 times resulting 15 experimental units. The data obtained were analyzed using an analysis of variance and if the treatment had a significant effect, it was followed by a Duncan Multiple Range Test (DMRT). The results showed that the effect of pH water for immersion had a significant effect on total rendement, water content, protein content, carbohydrate content, water absorption capacity, ash content, fat content, crude fiber content and oil absorption capacity. The best characteristic of the flour in this study was the cowpea flour that has been soaked pH 3 with 55.07% rendement, 1.80% water content, 3.66% ash content, 25.40% protein content, 1.09% fat content, 68.03% carbohydrates content, 10.68% fiber content, 2.11 ml/g water absorption and 1.66 ml/g oil absorption.